Exercícios físicos em portadores de neuropatia diabética : revisão sistemática e metanálise de ensaios clínicos randomizados - Maronesi, Caren Taís Piccoli (2015)
Introduction: Diabetes mellitus is considered a prevalent public health problem, with high social and economic burden. Among the most common complications, there is the Diabetic Neuropathy. The exercise interventions are associated with improvements in muscle strength, functional capacity and fatigue. Objective: To systematically review the effects of treatment with aerobic exercise, resistance or combined exercise (resistance / aerobic / balance) on the functional aspects and physical ability of patients with diabetic neuropathy. Methodology: A search was performed in electronic databases: MEDLINE (via PubMed), CENTRAL COCHRANE, LILACS (via Bireme) and PEDro of randomized clinical trials who underwent aerobic exercise, resistance exercise or exercise combined (resistance / aerobic / balance) compared with control group in patients with diabetic neuropathy. The outcomes considered were: balance evaluated from the ABC scale and the glycemic index by fasting and postprandial. Results: Of 389 studies identified, five were included, totaling 292 individuals. It was observed that the combined exercise (resistance / balance) compared with the control showed significant improvement in balance (8; 95% CI: 1.12, 14.88; I2 = 0%). Two of the five studies that evaluated the muscle strength of the lower limbs (n = 116), both studies using combined exercises (resistance / balance) vs. control, but could not perform a meta-analysis of these studies because muscle strength was evaluated in different ways. Only one article evaluated the postprandial glycemic index and glycemic index of fasting (n = 87), preventing the meta-analysis. In this study the postprandial glycemic index and fasting when comparing the two groups showed no significant difference. Conclusion: The data analyzed in this review demonstrated that the balance in subjects with diabetic neuropathy improved with the combined exercise